MODERN ISSUES OF FORMING INTERCULTURAL COMMUNICATIVE COMPETENCE IN FLT - Taubayev, Zh.T.; Yerlan, A.Y. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
In the context of Foreign Language Teaching (FLT), the development of Intercultural Communicative Competence (ICC) is essential for preparing students to navigate a diverse, interconnected world. This study explores modern challenges and strategies related to intercultural communicative competence formation, emphasizing the complexities posed by globalization, technological advancements, and the limited institutional support for intercultural communicative competence integration. Despite widespread recognition of intercultural communicative competence's importance, barriers such as inadequate teaching materials, curriculum constraints, and cultural identity tensions hinder its effective implementation. The research suggests that professional development, improved resources, and the strategic use of technology can enhance intercultural communicative competence teaching practices. Ultimately, fostering a more adaptable approach to intercultural communicative competence in foreign language teaching is crucial for cultivating culturally competent and communicatively proficient learners.
Keywords: Intercultural Communicative Competence; Foreign Language Teaching; globalization; technology in education